Educators’ Knowledge Transposition: the Algebra Devolution of Thinking - Maudy, Septiani Yugni; Ruli, Redo Martila (Jurnal Riset Pendidikan Matematika, 2025)
In mathematics learning, knowledge is in the form of meaning, and it is part of the transposition process so that it is situational and in the form of abstraction from the context of its use. The process begins with repersonalization (the process of mathematizing a mathematical concept as done by mathematicians) and recontextualization (provide a new mathematical context) so that it becomes knowledge that is a posteriori. The role of educators is so fundamental because it is related to the stages. This study is based on the hermeneutic phenomenology. Data collection is carried out in the form of documentation studies, observations, and reflective argumentative dialogue. The image of knowledge is collectively constructed, and the knowledge is emerged from conjoining understandings between educator and researcher. The educators’ experiences were traced from a reflective-argumentative dialogue to investigate what educators have done and what will be done in mathematics teaching practice. The researcher also examined the educators’ knowledge transposition in thinking algebraically. These were projected in three knowledge conceptions of educators' thinking process. There are at least five main issues revealed concerning knowledge for practice, knowledge in practice, and knowledge of practice. The transposition of educator knowledge becomes devolution of algebraic thinking from educators to students.